To tax or not to tax sin goods: that’s the question for emerging economies (2023)
In times of crisis and budgetary pressures, world governments (specially from emerging economies) look more decisively for alternative sources of income generation. One such alternative is the so-called “sin taxes’’. Many factors affect individual attitudes toward “legal vices” such as smoking, alcohol, gambling, plastic consumption, or consumption of beef, with religion having the greatest impact. Taxing the consumption of products or activities that pose a threat to the health of people and that cause damage to the environment has resulted in a lucrative, controversial strategy with variable results in the governments that have implemented it. This paper aims to use Scopus and Web of Science to systematically contrast how developed economies have implemented such types of taxes, which challenges those countries have faced and which lessons they can share with under developed countries. In the same way, this paper will present how, sometimes, taxes on sins do not discourage unhealthy behaviors nor are they a good way to increase government revenues.